2018
DOI: 10.12968/vetn.2018.9.9.497
|View full text |Cite
|
Sign up to set email alerts
|

The use of outcome measures in equine rehabilitation

Abstract: Background: The ideal goal of equine rehabilitation following injury or surgery is to return the horse to a level of function that either meets or exceeds the previous performance level, and monitoring progress is important within rehabilitation. Outcome measures (OM) are used extensively in human practice and research, especially patient reported outcomes (PRO). PROs generally consist of a series of questions and observation of functional tasks, use of which may be challenging in equine practice. Aim: The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…5 It is important to understand that the extent of thoracolumbar flexion is very much dependent on conformation and range of motion (ROM) of the spinal joints, 3 but previous studies have shown a linear increase in muscular electromyographic activity of both the m. longissimus dorsi and m. rectus abdominis alongside angle of incline of surface. [6][7][8] It is therefore postulated that recruitment of the stabilisation muscles during walking on an inclined WT should show an increase in facilitation and development of muscle across the thoracolumbar back profile in excess of that achieved on the flat. The aim of this study was therefore to assess the effect of recurring inclined WT sessions on equine epaxial muscles development.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is important to understand that the extent of thoracolumbar flexion is very much dependent on conformation and range of motion (ROM) of the spinal joints, 3 but previous studies have shown a linear increase in muscular electromyographic activity of both the m. longissimus dorsi and m. rectus abdominis alongside angle of incline of surface. [6][7][8] It is therefore postulated that recruitment of the stabilisation muscles during walking on an inclined WT should show an increase in facilitation and development of muscle across the thoracolumbar back profile in excess of that achieved on the flat. The aim of this study was therefore to assess the effect of recurring inclined WT sessions on equine epaxial muscles development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of detail regarding the specific physiotherapy interventions, such as for treatments including manual therapy [3], electrotherapy [1] or exercise therapy [4,5], either individually or in combination, varies between publications ranging from trials, often with low subject numbers to clinical review papers. As a result, equine physiotherapists use this information in combination with their experience and clinical reasoning to select treatment interventions they consider effective [6]. For example, in rehabilitation plans for overriding dorsal spinous processes, exercises to encourage ventral flexion to separate the spinous processes [7] are used in combination with exercises to strengthen the deeper 'core' stability muscle multifidus [8].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve comparable professional practice standards in equine physiotherapy, OMs must be incorporated into practice [6]. To date, a few equine specific OMs that measure a single factor in clinical practice (referred to as objective markers (OBJM)) have been subject to reliability testing but there are no composite equine OMs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations